EFFECT OF THREE DIFFERENT SCAPU- LAR POSITIONS ON ISOMETRIC STRENGTH AND MUSCLE ACTIVITY RA- TIO OF SERRATUS ANTERIOR IN SUB- JECTS WITH SCAPULAR WINGING - Nam, Ki-Seok (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to compare the isometric strength of serratus anterior at three different scapular positions (retracted, neutral and protracted) and electromyography activity ratio of upper tra- pezius to serratus anterior and upper trapezius to lower trapezius during isometric arm elevation between the subjects with and without scapular winging. Thirty-three subjects with scapular winging and thirty-three subjects without scapular winging were recruited for this study. This study showed that isometric strength of serratus ante- rior was significant decreased in subjects with scapular winging group than without scapular winging group (p